Integration of petroleum geology methods for oil and gas exploration - A. A. Polyakov; A. V. Stoupakova; N. A. Malyshev; R. S. Sautkin; V. E. Verzhbitsky; D. K. Komissarov; S. V. Osipov (Georesursy, 2024)
Integration of petroleum geology methods is the process of applying results of several methods for solving a task or group of tasks in order to reduce the limits of uncertainties in its solution. Since in the oil and gas industry there are a large number of methods, often aimed at solving similar problems, it is necessary to reduce the number of methods solving the same tasks. Thus, the integration of petroleum geology methods means the creation of exploration structures and algorithms for prediction of oil and gas contents. The system can be used not only to select a rational complex of exploration methods, but also to predict petroleum potential in the area by different methods, including IT technologies.